Production of Porous β-Type Ti–40Nb Alloy for Biomedical Applications: Comparison of Selective Laser Melting and Hot Pressing - Ksenia Zhuravleva (Materials, 2013)
We used selective laser melting (SLM) and hot pressing of mechanically-alloyed β-type Ti–40Nb powder to fabricate macroporous bulk specimens (solid cylinders). The total porosity, compressive strength, and compressive elastic modulus of the SLM-fabricated material were determined as 17% ± 1%, 968 ± 8 MPa, and 33 ± 2 GPa, respectively. The alloy’s elastic modulus is comparable to that of healthy cancellous bone. The comparable results for the hot-pressed material were 3% ± 2%, 1400 ± 19 MPa, and 77 ± 3 GPa. This difference in mechanical properties results from different porosity and phase composition of the two alloys. Both SLM-fabricated and hot-pressed cylinders demonstrated good in vitro biocompatibility. The presented results suggest that the SLM-fabricated alloy may be preferable to the hot-pressed alloy for biomedical applications, such as the manufacture of load-bearing metallic components for total joint replacements.